Pengaruh informasi akuntansi biaya terhadap nilai perusahaan serta implikasinya terhadap tanggungjawab perusahaan kepada stakeholder - Ulfatul Khasanah; Rina Sulistyowati; Agung Hirmantono; Mas’adah Mas’adah (Jurnal Ekonomi Modernisasi, 2020)
This study aims to obtain empirical evidence regarding the effect of cost accounting information on firm value and its implications for corporate responsibility to stakeholders. This research was conducted at consumer goods industrial sector companies listed on the IDX. The sample in this study consisted of 18 companies for 5 years, so that the data processed in this study were 90 data. Data analysis techniques using path analysis. The results showed that the indirect effect of the variable production costs on interest expense through firm value was non-significant. Meanwhile, the indirect effect of the production costs on tax expense through firm value is significant. Likewise, the indirect effect of the production costs variable on dividends through firm value, which is also significant. The research results can be considered for the company in terms of debt policy and dividend policy and for the government in determining taxes.